Given
![-6=-20-v](https://img.qammunity.org/2023/formulas/mathematics/college/64b960by9tr8z0cqtvk9y6755ez0hmxpyt.png)
- For -72 = 9(-20 - v):
![\begin{gathered} -(72)/(9)=(9(-20-v))/(9) \\ -8=-20-v \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5o3q12oysk99izixjf6zla5c0i35f6bcwl.png)
The equation is not equivalent
- For -90 = 15(-20 - v):
![\begin{gathered} (-90)/(15)=(15(-20-v))/(15) \\ -6=-20-v \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nodujyhf4zgd49nsy97f7q8xy7lvtt9qio.png)
The equation is equivalent
- For 5 * -6 = -100 - 5v:
Common factor 5
![\begin{gathered} -30=5(-20-v) \\ (-30)/(5)=(5(-20-v))/(5) \\ -6=-20-v \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u4k5hd3msew8uj8l3kpygaosii0ey001tq.png)
The equation is equivalent
- For 3 * -6 = -60 - 3v:
Common factor 3
![\begin{gathered} -18=3(-20-v) \\ (-18)/(3)=(3(-20-v))/(3) \\ -6=-20-v \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9dzt8lh8l970qg91tub69ah9kbupfpctv3.png)
The equation is equivalent
Answer:
-90 = 15(-20 - v)
5 * -6 = -100 - 5v
3 * -6 = -60 - 3v